AN ANALYSIS OF COHESION IN SHORT STORY “THE GIFT OF MAGI” - Zainuddin Zainuddin (English Education : English Journal for Teaching and Learning, 2018)
The researcher focuses the study on an analysis of Cohesion in short Story “The Gift of Magi”. The research is done through descriptive qualitative, in which the aims of the research are to describe the cohesion in short story, and then to determine the cohesion used dominantly in short story. Consequently, the researcher needs short story “The Gift of Magi” for primary data, and then some related Journals and books about Cohesion. Furthermore, the researcher uses content analysis method for analyzing the data. There the technique of analyzing the data; Reading the story, Analyzing cohesion in the story, and taking conclusion of overall discussion.